Bismuth ferrite-based energy storage ceramic with high entropy design as well as preparation method and application of bismuth ferrite-based energy storage ceramic

Through high entropy design, a variety of elements are introduced into bismuth ferrate-based ceramics, which solves the problems of high residual polarization strength, high dielectric loss and low breakdown electric field of the material, and achieves the improvement of high energy storage density and efficiency.

CN119613099AActive Publication Date: 2025-03-14ANHUI UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411762804.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-14
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Bismuth ferrate-based ceramic materials have problems such as high residual polarization strength, high dielectric loss and low breakdown electric field, resulting in limited energy storage performance and efficiency.

Method used

Using a high entropy design strategy, by introducing a variety of elements, such as NaNbO3 and MnO2, to the bismuth ferrate-based ceramics, the ratio of element doping is controlled, the relaxation characteristics are promoted, the polarization hysteresis is reduced, and the energy storage density and efficiency are improved.

Benefits of technology

The high energy storage density and efficiency of bismuth ferrate-based ceramics are achieved, the breakdown electric field is improved, the dielectric loss is reduced, and the comprehensive energy storage performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613099A_ABST
    Figure CN119613099A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric energy storage device materials, in particular to high-entropy designed bismuth ferrite-based energy storage ceramic as well as a preparation method and application thereof, the chemical composition formula of the material is (0.7-x) Bi < 0.9 > (Sm < 0.5 > Gd < 0.5 >) < 0.1 > FeO < 3-0.3 > (Sr < 0.5 > Ba < 0.5 >) TiO < 3-x > NaNbO < 3-y > MnO < 2 >, the value range of x is 0-0.15, and the value range of y is 0-0.005. The relaxation ferroelectric material is designed by adopting a high-entropy strategy, and various elements occupy the same site of the material to generate lattice distortion, so that the relaxation characteristic of bismuth ferrite-based ceramic is promoted, and a ferroelectric hysteresis loop is optimized. The NaNbO3 anti-ferroelectric material is introduced, the long-range ferroelectric order is destroyed, the local random field is enhanced, and a low Pr value can be obtained. And in addition, the concentration of oxygen vacancies can be reduced by properly adding 0.5% mol of MnO2, so that the leakage current of the material is reduced, the energy storage efficiency is improved, and the material design not only enriches the application field of the high-entropy ceramic, but also provides a new thought for improving the performance of the energy storage ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dielectric energy storage device materials, and in particular to a high-entropy designed bismuth ferrite-based energy storage ceramic, a preparation method and applications thereof. Background Art

[0002] With the development of modern power electronics technology, higher requirements are placed on the energy storage density and power density of dielectric materials. Especially in the fields of high-power pulse power systems, aerospace, and new energy vehicles, there is an increasing demand for high-temperature stability and reliability of ceramic capacitors. Traditional ceramic materials have been unable to meet the increasingly demanding application environment due to their low Curie temperature and limited energy storage performance. Therefore, it is particularly important to develop new ceramic materials with excellent high-temperature energy storage performance and stability. As an emerging material field, high-entropy ceramics have attracted widespread attention in recent years. Their unique chemical composition and structural design provide new possibilities for achieving high energy storage density. Compared with other dielectric energy storage materials, bismuth ferrite-based ceramics, as a lead-free material, not only have environmental advantages, but also have the advantages of fast charging and discharging capabilities, high power density, and long cycle life, providing a promising alternative to lead-based ceramics.

[0003] Bismuth ferrite-based ceramics (BiFeO3) have a high Curie temperature (T C ), high Curie temperature is crucial to ensure the reliability and stability of the material over a wide temperature range; bismuth ferrite-based ceramics have a large spontaneous polarization (about 100μC / cm 2 ), this feature helps to improve the energy storage density of the material. A large spontaneous polarization intensity means that under the action of an electric field, the material can produce a larger polarization, thereby storing more energy. However, it has a large residual polarization intensity, which also leads to its relatively low breakdown field strength, and also limits the improvement of efficiency. In August 2024, "ACS Applied Materials&Interfaces" published an article titled "High-Entropy Strategy for Improved Mechanical and Energy StorageProperties in BaTiO3-BiFeO3 Based Ceramics". The study developed a lead-free ferroelectric ceramic material based on 0.67BiFeO3-0.33BaTiO3, and introduced Sr(Mg) through the traditional solid-phase sintering method. 1 / 6 Zn 1 / 6 Ta 1 / 3Nb 1 / 3 )O3, achieving multi-element coexistence and high configuration entropy at the B site, and achieving an excellent energy storage efficiency (η) of 75% and 2.4 J / cm 3 The recoverable energy storage density (Wrec ), and also achieved an ultra-high hardness of up to 7.2 GPa, which confirms that the high-entropy strategy of the invention is effective.

[0004] In summary, bismuth ferrite-based ceramics, as a potential lead-free system to replace lead-based ceramics, have important environmental and health advantages.

[0005] In view of the above difficulties, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of high residual polarization strength, dielectric loss, low breakdown electric field, etc. of bismuth ferrite-based ceramics by using high entropy strategy, thereby improving the comprehensive energy storage performance, and provide a high entropy design of bismuth ferrite-based energy storage ceramics, preparation method and application thereof. This material design not only enriches the application field of high entropy ceramics, but also provides a new idea for improving the performance of energy storage ceramics.

[0007] In order to achieve the above object, the present invention discloses a high entropy design bismuth ferrite-based energy storage ceramic, wherein the chemical composition of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic is (0.7-x)Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-xNaNbO3-yMnO2, where 0≤x≤0.15, 0≤y≤0.005.

[0008] The x is 0, 0.05, 0.10 or 0.15, and the y is 0 or 0.005.

[0009] The present invention also discloses a method for preparing the high entropy designed bismuth ferrite-based energy storage ceramic, comprising the following steps:

[0010] S1, drying Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, and Fe2O3, and mixing them according to the proportion to obtain a mixture A;

[0011] S2, the mixture A obtained in step S1 is subjected to a first ball milling with deionized water and zirconium oxide balls, and then dried after ball milling, and after being completely dried, is passed through a 120-mesh sieve to obtain a mixture B;

[0012] S3, pre-calcining the mixture B obtained in step S2 at 880°C for 3h, cooling it in the furnace after the temperature drops to 300°C, and then ball-milling it for the second time, drying it, and then passing it through a 120-mesh sieve to obtain a high entropy powder;

[0013] S4, pressing the high entropy powder obtained in step S3 into a cylindrical ceramic body with a diameter of 10 mm, and sintering it in a muffle furnace at 970° C.-990° C. to obtain a high entropy designed bismuth ferrite-based energy storage ceramic.

[0014] In step S2, during the first ball milling, the planetary ball mill was milled clockwise for 12 hours, and after waiting for 0.5 hours, the ball milling was continued counterclockwise for 12 hours at a rotation speed of 200 r / min. After the ball milling, the ball was dried for 48 hours at a drying temperature of 80°C.

[0015] In the step S3, before the second ball milling, 0-0.5 mol% MnO2 is added to the pre-sintered powder to form a mixture.

[0016] In step S3, during the second ball milling, the planetary ball mill mills clockwise for 12 hours, waits for 0.5 hours, and then continues to mill counterclockwise for 12 hours at a rotation speed of 200 r / min. After the ball milling, the ball is dried for 48 hours at a drying temperature of 80°C.

[0017] In the step S4, the sieved high entropy powder is mixed with 7 wt% of PVA binder to form granules, and then sieved through a 120-mesh sieve again to obtain a ceramic body under a pressure of 158 MPa, with a holding time of 2 minutes.

[0018] In step S4, the specific sintering process is as follows: bury the ceramic body in the same calcined powder, heat the temperature to 970-990°C at a heating rate of 4-6°C / min, sinter for 2-3h, cool the temperature to 300°C, and obtain a high-entropy designed bismuth ferrite-based energy storage ceramic.

[0019] The present invention also discloses the application of the high entropy designed bismuth ferrite-based energy storage ceramic in high-power dielectric energy storage material devices.

[0020] Based on the high polarization characteristics of BiFeO3 and the excellent dielectric properties of BaTiO3, the present invention controls the proportion of multiple element doping through the high entropy design principle, which can promote the relaxation characteristics of bismuth ferrite-based ceramics, reduce polarization hysteresis, and achieve higher energy storage density and efficiency. The lattice distortion and resistivity increase caused by the high entropy effect help to enhance the breakdown electric field and further improve the energy storage performance.

[0021] The main difficulty in the process of the present invention is to solve the problem that during the sintering process, Bi 3+ The volatilization of Fe leads to an increase in leakage current and 3+ The change in valence leads to an increase in the concentration of defective ions, which reduces the density of the ceramic and the discharge energy and efficiency. The research process uses a sealed sintering method to bury the pressed green body in the pre-burned powder, reducing the Bi 3+The introduction of NaNbO3 can be used as a sintering aid to reduce the sintering temperature and promote the densification of ceramics. Doping with appropriate amounts of Sm and Gd elements can also stabilize Fe 3+ The price change.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 3+ 、Sm 3+ , Gd 3+ , Sr 2+ , Ba 2 + 、Na + ) and B position (Nb 5+ 、Ti 4+ , Fe 3+ ) The coexistence of multiple elements increases the configurational entropy of the ceramic material, thereby inducing the relaxation behavior of BiFeO3-based ferroelectrics; the microscopic crystal structure of the high-entropy ceramic may tend to decrease due to the reduction of the heterogeneity of the local electric field. The reduction of local heterogeneity can be attributed to the slow diffusion effect induced by the configurational entropy. On the one hand, the introduction of NN helps to achieve a quasi-linear polarization response with almost no hysteresis under high electric fields, which is crucial for improving energy storage efficiency. The increase in NN content will lead to random distribution of A-site and B-site ions, destroying the long-range ferroelectric order to form short-range PNR, thereby achieving fast discharge response and low P r In addition, the appropriate addition of 0.5% mol of MnO2 can reduce the concentration of oxygen vacancies, thereby reducing the leakage current of the material and improving the energy storage efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The sintered XRD images of different bismuth ferrite-based high entropy relaxor ferroelectric energy storage ceramics prepared in Examples 1 to 5;

[0024] Figure 2 The SEM images of different bismuth ferrite-based high entropy relaxor ferroelectric energy storage ceramics prepared in Examples 1 to 5, wherein (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, (e) Example 5;

[0025] Figure 3 The hysteresis loop images of different bismuth ferrite-based high entropy relaxor ferroelectric energy storage ceramics prepared in Examples 1 to 5;

[0026] Figure 4 The dielectric constant and dielectric loss images at 1 MHz of different bismuth ferrite-based high entropy relaxation ferroelectric energy storage ceramics prepared in Examples 1 to 5;

[0027] Figure 5The energy storage performance pictures of the bismuth ferrite-based high entropy relaxation ferroelectric energy storage ceramics prepared in Example 5, wherein (a) is a picture of the unipolar hysteresis loop of the high entropy designed bismuth ferrite-based ceramic sample prepared in Example 5 under different electric fields, and (b) is a picture of the W in Example 5. rec ,W tal and η vary with the electric field;

[0028] Figure 6 Figure 5 is a charge and discharge performance picture of the bismuth ferrite-based high entropy relaxation ferroelectric energy storage ceramic prepared in Example 5, wherein (a) is the underdamped charge and discharge current curve of the high entropy bismuth ferrite-based ceramic sample prepared in Example 5, and (b) is the high entropy bismuth ferrite-based ceramic sample I prepared in Example 5. max , C D , P D The curves of the change with the electric field, (c) is the over-damped charge and discharge current curve of the high entropy bismuth ferrite-based ceramic sample prepared in Example 5, and (d) is the high entropy bismuth ferrite-based ceramic sample W prepared in Example 5 D Curves changing over time. DETAILED DESCRIPTION

[0029] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0030] Example 1

[0031] This embodiment provides a high entropy design bismuth ferrite-based relaxor ferroelectric energy storage ceramic, the chemical composition of the ceramic is 0.7Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3.

[0032] The specific preparation steps of the ceramic are as follows:

[0033] Ingredients: Put the chemical raw materials Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, and Fe2O3 (the purity of Bi2O3, Sm2O3, Gd2O3, TiO2, and Na2CO3 is not less than 99.99%, and the purity of SrCO3, BaCO3, Nb2O5, and Fe2O3 is not less than 99.9%) into a drying oven and dry them at a constant temperature of 80°C for 48 hours to remove the moisture in the raw materials, and then accurately weigh them on an electronic balance according to the formula ratio of each element.

[0034] Primary ball milling: Pour the zirconia balls, the weighed raw material mixture and deionized water into a nylon jar in sequence, then place the jar in a planetary ball mill, mill clockwise for 12 h, stop for 0.5 h, and then mill counterclockwise for 12 h at a speed of 200 r / min.

[0035] Drying: The mixture of the ball-milled raw materials and deionized water was separated from the ball-milling beads through a filter, and then the mixture was poured into a crystallization dish and dried in a drying oven at a constant temperature of 80° C. for 48 hours.

[0036] Sieving: When the mixture is completely dry and only the raw material powder remains, take the powder out of the crystallization dish and grind it using an agate mortar until all the powder passes through a 120-mesh sieve to obtain a powder with uniform particle size.

[0037] Pre-sintering: The sieved sample was placed in an alumina crucible, and several small holes were reserved in the powder to discharge the carbon dioxide released during the pre-sintering process. After that, the sample was pre-sintered in a muffle furnace at 880°C for 3 hours.

[0038] Secondary ball milling and sieving: Repeat the first ball milling, drying and sieving process to obtain a powder with uniform particle distribution.

[0039] Tabletting: Add 7wt% PVA binder to the powder after the second screening to granulate, and pass through a 120-mesh sieve again after granulation to obtain the final powder. Take an appropriate amount of powder and put it into a mold, and use an automatic tablet press to press out a cylindrical green body with a diameter of 10mm, with a pressure of 158Mpa and a holding time of 2min.

[0040] Debinding: All the blanks were placed in a muffle furnace and heated to 600°C at a heating rate of 2°C / min. After keeping warm for 3 hours, the cooling rate was controlled to 5°C / min. After the temperature dropped to 300°C, it was cooled in the furnace to room temperature.

[0041] Sintering: The ceramic body of the component after debinding is buried in the same calcined powder, placed in a muffle furnace and heated to 990°C at a heating rate of 5°C / min, the sintering time is 3h, the cooling rate is 5°C / min, then dropped to 300°C and cooled to room temperature with the furnace to obtain a ceramic sample of the component.

[0042] Sample preparation: The ceramic sample is crushed, polished, treated with alcohol ultrasound, coated with silver paste on both sides, etc. to obtain the sample to be tested.

[0043] In the steps, the specific radius of silver paste applied on both sides is 1 mm and 2 mm respectively. The silver burning temperature is 700° C. and the time is 40 minutes.

[0044] The XRD image of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows a P4mm tetragonal phase structure.

[0045] The surface SEM morphology picture of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows relatively dense grains with an average grain size of 1.85 μm.

[0046] The bismuth ferrite-based relaxor ferroelectric energy storage ceramic sample prepared in this embodiment can release energy storage density W rec 1.96 J / cm 3 The energy storage efficiency η is 42.93%, the breakdown field strength is 230kV / cm, and the relative dielectric constant ε r It is 1471.2, and the dielectric loss tanδ is 0.085.

[0047] Example 2

[0048] This embodiment provides a high entropy design bismuth ferrite-based relaxor ferroelectric energy storage ceramic, the chemical composition of the ceramic is 0.65Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-0.05NaNbO3.

[0049] The specific preparation steps of the ceramic are as follows:

[0050] Ingredients: Put the chemical raw materials Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, and Fe2O3 (the purity of Bi2O3, Sm2O3, Gd2O3, TiO2, and Na2CO3 is not less than 99.99%, and the purity of SrCO3, BaCO3, Nb2O5, and Fe2O3 is not less than 99.9%) into a drying oven and dry them at a constant temperature of 80°C for 48 hours to remove the moisture in the raw materials, and then accurately weigh them on an electronic balance according to the formula ratio of each element.

[0051] Primary ball milling: Pour the zirconia balls, the weighed raw material mixture and deionized water into a nylon jar in sequence, then place the jar in a planetary ball mill, mill clockwise for 12 h, stop for 0.5 h, and then mill counterclockwise for 12 h at a speed of 200 r / min.

[0052] Drying: The mixture of the ball-milled raw materials and deionized water was separated from the ball-milling beads through a filter, and then the mixture was poured into a crystallization dish and dried in a drying oven at a constant temperature of 80° C. for 48 hours.

[0053] Sieving: When the mixture is completely dry and only the raw material powder remains, take the powder out of the crystallization dish and grind it using an agate mortar until all the powder passes through a 120-mesh sieve to obtain a powder with uniform particle size.

[0054] Pre-sintering: The sieved sample was placed in an alumina crucible, and several small holes were reserved in the powder to discharge the carbon dioxide released during the pre-sintering process. After that, the sample was pre-sintered in a muffle furnace at 880°C for 3 hours.

[0055] Secondary ball milling and sieving: Repeat the first ball milling, drying and sieving process to obtain a powder with uniform particle distribution.

[0056] Tabletting: Add 7wt% PVA binder to the powder after the second screening to granulate, and pass through a 120-mesh sieve again after granulation to obtain the final powder. Take an appropriate amount of powder and put it into a mold, and use an automatic tablet press to press out a cylindrical green body with a diameter of 10mm, with a pressure of 158Mpa and a holding time of 2min.

[0057] Debinding: All the blanks were placed in a muffle furnace and heated to 600°C at a heating rate of 2°C / min. After keeping warm for 3 hours, the cooling rate was controlled to 5°C / min. After the temperature dropped to 300°C, it was cooled in the furnace to room temperature.

[0058] Sintering: The ceramic body of the component after debinding is buried in the same calcined powder, placed in a muffle furnace and heated to 990°C at a heating rate of 5°C / min, the sintering time is 3h, the cooling rate is 5°C / min, then dropped to 300°C and cooled to room temperature with the furnace to obtain a ceramic sample of the component.

[0059] Sample preparation: The ceramic sample is crushed, polished, treated with alcohol ultrasound, coated with silver paste on both sides, etc. to obtain the sample to be tested.

[0060] In the steps, the specific radius of silver paste applied on both sides is 1 mm and 2 mm respectively. The silver burning temperature is 700° C. and the time is 40 minutes.

[0061] The XRD images of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example show tetragonal phase P4mm and pseudo cubic phase Structural coexistence.

[0062] The surface SEM morphology picture of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows relatively dense grains with an average grain size of 0.54 μm.

[0063] The bismuth ferrite-based relaxor ferroelectric energy storage ceramic sample prepared in this embodiment can release energy storage density W rec 2.33 J / cm 3, the energy storage efficiency η is 45.46%, the breakdown field strength is 260kV / cm, and the relative dielectric constant ε r It is 1397.38, and the dielectric loss tanδ is 0.082.

[0064] Example 3

[0065] This embodiment provides a high entropy design bismuth ferrite-based relaxor ferroelectric energy storage ceramic, the chemical composition of the ceramic is 0.6Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-0.1NaNbO3.

[0066] The specific preparation steps of the ceramic are as follows:

[0067] Ingredients: Chemical raw materials Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, Fe2O3 (wherein the purity of Bi2O3, Sm2O3, Gd2O3, TiO2, Na2CO3 is not less than 99.99%),

[0068] The purity of SrCO3, BaCO3, Nb2O5, and Fe2O3 is not less than 99.9%), and is placed in a drying oven and dried at a constant temperature of 80°C for 48 hours to remove the moisture in the raw materials, and then accurately weighed on an electronic balance according to the formula ratio of each element.

[0069] Primary ball milling: Pour zirconia balls, weighed raw materials and deionized water into a nylon jar in sequence, then place the jar in a planetary ball mill, mill clockwise for 12 hours, stop for 0.5 hours, and then mill counterclockwise for 12 hours at a speed of 200 r / min.

[0070] Drying: The mixture of the ball-milled raw materials and deionized water was separated from the ball-milling beads through a filter, and then the mixture was poured into a crystallization dish and dried in a drying oven at a constant temperature of 80° C. for 48 hours.

[0071] Sieving: When the mixture is completely dry and only the raw material powder remains, take the powder out of the crystallization dish and grind it using an agate mortar until all the powder passes through a 120-mesh sieve to obtain a powder with uniform particle size.

[0072] Pre-sintering: The sieved sample was placed in an alumina crucible, and several small holes were reserved in the powder to discharge the carbon dioxide released during the pre-sintering process. After that, the sample was pre-sintered in a muffle furnace at 880°C for 3 hours.

[0073] Secondary ball milling and sieving: Repeat the first ball milling, drying and sieving process to obtain a powder with uniform particle distribution.

[0074] Tabletting: Add 7wt% PVA binder to the powder after the second screening to granulate, and pass through a 120-mesh sieve again after granulation to obtain the final powder. Take an appropriate amount of powder and put it into a mold, and use an automatic tablet press to press out a cylindrical green body with a diameter of 10mm, with a pressure of 158Mpa and a holding time of 2min.

[0075] Debinding: All the blanks were placed in a muffle furnace and heated to 600°C at a heating rate of 2°C / min. After keeping warm for 3 hours, the cooling rate was controlled to 5°C / min. After the temperature dropped to 300°C, it was cooled in the furnace to room temperature.

[0076] Sintering: The ceramic body of the component after debinding is buried in the same calcined powder, placed in a muffle furnace and heated to 985°C at a heating rate of 5°C / min, the sintering time is 3h, the cooling rate is 5°C / min, then dropped to 300°C and cooled to room temperature with the furnace to obtain a ceramic sample of the component.

[0077] Sample preparation: The ceramic sample is crushed, polished, treated with alcohol ultrasound, coated with silver paste on both sides, etc. to obtain the sample to be tested.

[0078] In the steps, the specific radius of silver paste applied on both sides is 1 mm and 2 mm respectively. The silver burning temperature is 700° C. and the time is 40 minutes.

[0079] From the XRD image of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example, it can be seen that the tetragonal phase P4mm and the second phase (Sm, Gd)3NbO7 coexist.

[0080] The surface SEM morphology picture of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows relatively dense grains with an average grain size of 0.51 μm.

[0081] The bismuth ferrite-based relaxor ferroelectric energy storage ceramic sample prepared in this embodiment can release energy storage density W rec 3.5J / cm 3 , energy storage efficiency η is 56.7%, breakdown field strength is 330kV / cm, relative dielectric constant ε r It is 844.29, and the dielectric loss tanδ is 0.073.

[0082] Example 4

[0083] This embodiment provides a high entropy design bismuth ferrite-based relaxor ferroelectric energy storage ceramic, the chemical composition of the ceramic is 0.55Bi 0.9 (Sm 0.5 G 0.5) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-0.15NaNbO3.

[0084] The specific preparation steps of the ceramic are as follows:

[0085] Ingredients: Chemical raw materials Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, Fe2O3 (wherein the purity of Bi2O3, Sm2O3, Gd2O3, TiO2, Na2CO3 is not less than 99.99%),

[0086] The purity of SrCO3, BaCO3, Nb2O5, and Fe2O3 is not less than 99.9%), and is placed in a drying oven and dried at a constant temperature of 80°C for 48 hours to remove the moisture in the raw materials, and then accurately weighed on an electronic balance according to the formula ratio of each element.

[0087] Primary ball milling: Pour zirconia balls, weighed raw materials and deionized water into a nylon jar in sequence, then place the jar in a planetary ball mill, mill clockwise for 12 hours, stop for 0.5 hours, and then mill counterclockwise for 12 hours at a speed of 200 r / min.

[0088] Drying: The mixture of the ball-milled raw materials and deionized water was separated from the ball-milling beads through a filter, and then the mixture was poured into a crystallization dish and dried in a drying oven at a constant temperature of 80° C. for 48 hours.

[0089] Sieving: When the mixture is completely dry and only the raw material powder remains, take the powder out of the crystallization dish and grind it using an agate mortar until all the powder passes through a 120-mesh sieve to obtain a powder with uniform particle size.

[0090] Pre-sintering: The sieved sample was placed in an alumina crucible, and several small holes were reserved in the powder to discharge the carbon dioxide released during the pre-sintering process. After that, the sample was pre-sintered in a muffle furnace at 880°C for 3 hours.

[0091] Secondary ball milling and sieving: Repeat the first ball milling, drying and sieving process to obtain a powder with uniform particle distribution.

[0092] Tabletting: Add 7wt% PVA binder to the powder after the second screening to granulate, and pass through a 120-mesh sieve again after granulation to obtain the final powder. Take an appropriate amount of powder and put it into a mold, and use an automatic tablet press to press out a cylindrical green body with a diameter of 10mm, with a pressure of 158Mpa and a holding time of 2min.

[0093] Debinding: All the blanks were placed in a muffle furnace and heated to 600°C at a heating rate of 2°C / min. After keeping warm for 3 hours, the cooling rate was controlled to 5°C / min. After the temperature dropped to 300°C, it was cooled in the furnace to room temperature.

[0094] Sintering: The ceramic body of the component after debinding is buried in the same calcined powder, placed in a muffle furnace and heated to 970°C at a heating rate of 5°C / min, the sintering time is 3h, the cooling rate is 5°C / min, then dropped to 300°C and cooled to room temperature with the furnace to obtain a ceramic sample of the component.

[0095] Sample preparation: The ceramic sample is crushed, polished, treated with alcohol ultrasound, coated with silver paste on both sides, etc. to obtain the sample to be tested.

[0096] In the steps, the specific radius of silver paste applied on both sides is 1 mm and 2 mm respectively. The silver burning temperature is 700° C. and the time is 40 minutes.

[0097] The XRD images of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this embodiment show that the tetragonal phase P4mm, And (Sm,Gd)3NbO7 three phases coexist.

[0098] The surface SEM morphology picture of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows relatively dense grains with an average grain size of 0.46 μm.

[0099] The bismuth ferrite-based relaxor ferroelectric energy storage ceramic sample prepared in this embodiment can release energy storage density W rec 2.5J / cm 3 , energy storage efficiency η is 79%, breakdown field strength is 290kV / cm, relative dielectric constant ε r It is 652.89, and the dielectric loss tanδ is 0.084.

[0100] Example 5

[0101] This embodiment provides a high entropy design bismuth ferrite-based relaxor ferroelectric energy storage ceramic, the chemical composition of the ceramic is 0.6Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-0.1NaNbO3-0.5mol%MnO2.

[0102] The specific preparation steps of the ceramic are as follows:

[0103] Ingredients: Put the chemical raw materials Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, and Fe2O3 (the purity of Bi2O3, Sm2O3, Gd2O3, TiO2, and Na2CO3 is not less than 99.99%, and the purity of SrCO3, BaCO3, Nb2O5, and Fe2O3 is not less than 99.9%) into a drying oven and dry them at a constant temperature of 80°C for 48 hours to remove the moisture in the raw materials, and then accurately weigh them on an electronic balance according to the formula ratio of each element.

[0104] Primary ball milling: Pour zirconia balls, weighed raw materials and deionized water into a nylon jar in sequence, then place the jar in a planetary ball mill, mill clockwise for 12 hours, stop for 0.5 hours, and then mill counterclockwise for 12 hours at a speed of 200 r / min.

[0105] Drying: The mixture of the ball-milled raw materials and deionized water was separated from the ball-milling beads through a filter, and then the mixture was poured into a crystallization dish and dried in a drying oven at a constant temperature of 80° C. for 48 hours.

[0106] Sieving: When the mixture is completely dry and only the raw material powder remains, take the powder out of the crystallization dish and grind it using an agate mortar until all the powder passes through a 120-mesh sieve to obtain a powder with uniform particle size.

[0107] Pre-sintering: The sieved sample is placed in an alumina crucible, and several small holes are reserved in the powder to discharge the carbon dioxide released during the pre-sintering process. Then the sample is pre-sintered in a muffle furnace at 880°C for 3 hours.

[0108] Secondary ball milling and sieving: 0.5 mol% MnO2 is added to the pre-calcined powder, and the first ball milling, drying and sieving process is repeated to obtain a powder with uniform particle distribution.

[0109] Tabletting: Add 7wt% PVA binder to the powder after the second screening to granulate, and pass through a 120-mesh sieve again after granulation to obtain the final powder. Take an appropriate amount of powder and put it into a mold, and use an automatic tablet press to press out a cylindrical green body with a diameter of 10mm, with a pressure of 158Mpa and a holding time of 2min.

[0110] Debinding: All the blanks were placed in a muffle furnace and heated to 600°C at a heating rate of 2°C / min. After keeping warm for 3 hours, the cooling rate was controlled to 5°C / min. After the temperature dropped to 300°C, it was cooled in the furnace to room temperature.

[0111] Sintering: The ceramic body of the component after debinding is buried in the same calcined powder, placed in a muffle furnace and heated to 980°C at a heating rate of 5°C / min, the sintering time is 3h, the cooling rate is 5°C / min, then dropped to 300°C and cooled to room temperature with the furnace to obtain a ceramic sample of the component.

[0112] Sample preparation: The ceramic sample is crushed, polished, treated with alcohol ultrasound, coated with silver paste on both sides, etc. to obtain the sample to be tested.

[0113] In the sample preparation step, silver paste was applied on both sides with specific radius of 1 mm and 2 mm respectively. The silver calcination temperature was 700°C and the time was 40 min.

[0114] The XRD image of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows tetragonal phase P4mm and pseudo cubic phase coexist.

[0115] The surface SEM morphology picture of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic material prepared in this example shows dense grains with an average grain size of 0.49 μm.

[0116] The bismuth ferrite-based relaxor ferroelectric energy storage ceramic sample prepared in this embodiment can release energy storage density W rec 3.7J / cm 3 , energy storage efficiency η is 70.5%, breakdown field strength is 330kV / cm, relative dielectric constant ε r The dielectric loss tanδ is 840.1, the dielectric loss tanδ is 0.06, and the discharge time is 33ns.

[0117] The bismuth ferrite-based ceramic samples in Examples 1-5 were subjected to XRD, SEM, dielectric temperature spectrum, hysteresis loop, and charge-discharge tests, and the results were analyzed as follows:

[0118] Figure 1 XRD images of the high entropy designed bismuth ferrite-based ceramic samples prepared in Examples 1-5: The phase structure of the ceramic sample without NaNbO3 is P4mm, and the main structure of the ceramic samples with x=0.05, 0.10, and 0.15 is P4mm, and part of it is converted into Structure, there is part of (Sm, Gd)3NbO7 impurity phase inside the ceramic samples with x=0.10 and 0.15. When 0.5% mol MnO2 is added to the ceramic sample with component x=0.1, no obvious (Sm, Gd)3NbO7 impurity phase appears. The addition of MnO2 may help to inhibit the formation of impurity phase in the material, thereby maintaining the phase purity of the material and the integrity of the crystal structure.

[0119] Figure 2SEM images of the high entropy designed bismuth ferrite-based ceramic samples prepared in Examples 1-5, specifically, (a) is a SEM image of the high entropy designed bismuth ferrite-based ceramic in Example 1, with an average grain size of 1.85 μm. (b) is a SEM image of the high entropy designed bismuth ferrite-based ceramic in Example 2, with an average grain size of 0.64 μm. (c) is a SEM image of the high entropy designed bismuth ferrite-based ceramic in Example 3, with an average grain size of 0.51 μm. (d) is a SEM image of the high entropy designed bismuth ferrite-based ceramic in Example 4, with an average grain size of 0.46 μm. (e) is a SEM image of the high entropy designed bismuth ferrite-based ceramic in Example 5, with an average grain size of 0.49 μm. Figures (a)-(d) show that the average grain size gradually decreases, which helps to improve the breakdown electric field of the ceramic. Figure (e) shows that the average grain size of the sample with the addition of MnO2 is also reduced.

[0120] Figure 3 The dielectric constant and dielectric loss graph of the high entropy designed bismuth ferrite-based ceramic samples prepared in Examples 1-5 at 1MHz, the maximum dielectric constant of the ceramic value at x=0 is 1397.38, and gradually decreases to the maximum dielectric constant of the ceramic with component x=0.15 is 840.1, indicating that after the addition of NaNbO3, the dielectric constant gradually changes and tends to be flat, indicating that it is affected by relaxation behavior. In Examples 1-5, the dielectric loss value is low at low temperature, and the loss value gradually increases with the increase of temperature. The increase in temperature increases the mobility of charge carriers, which increases the conductivity of the material and thus increases the dielectric loss.

[0121] Figure 4 The hysteresis loop images of the high entropy designed bismuth ferrite-based ceramic samples prepared in Examples 1-5. As the NaNbO3 doping content gradually increases (x≤0.1), the P r Gradually decrease, P m and E b In Example 4, the doping amount of NaNbO3 is 0.15, P r , E b The further decrease may be related to the lattice distortion induced by NaNbO3 and the increase of random electric field. In addition, under the action of the second phase, the breakdown field strength is affected and reduced accordingly. The P of Example 4 r The value reaches the lowest, about 3μC / cm 2 By calculating the energy density and energy consumption, it is found that in Example 4, when x=0.15, an ESP (W) with a breakdown strength of 290 kV / cm is obtained. rec ~2.5J / cm 3 ; η~79%) performance, in Example 5, when x=0.1, ESP (W rec~3.7J / cm 3 ;η~70.4%) performance.

[0122] Figure 5 (a) is a picture of the unipolar hysteresis loop of the high entropy designed bismuth ferrite-based ceramic sample prepared in Example 5 under different electric fields. The maximum polarization value and energy storage density increase with the increase of the electric field. Figure 5 (b) is W in Example 5 rec ,W tal The energy storage efficiency and energy storage density have opposite trends of change as η and η change with the electric field. Under high electric field, the electric domain may be more responsive and switch quickly, which helps to increase the discharge rate and energy storage density. But at the same time, this rapid response may lead to increased energy loss, thereby reducing the energy storage efficiency.

[0123] Figure 6 (a) is the underdamped charge-discharge current curve of the high entropy bismuth ferrite-based ceramic sample prepared in Example 5, Figure 6 (b) is the high entropy bismuth ferrite-based ceramic sample I prepared in Example 5 max , C D , P D The curve of electric field change, Figure 6 (c) is the overdamped charge-discharge current curve of the high-entropy bismuth ferrite-based ceramic sample prepared in Example 5, Figure 6 (d) is the high entropy bismuth ferrite-based ceramic sample W prepared in Example 5 D The curve changes with time. The results show that C D and P D Both increase with the increase of electric field and reach 679.3A / cm at 160kV / cm. 2 and 54.34MW / cm 3 The maximum value of the discharge time t 0.9 = 33ns, which indicates that the discharge energy density (W d ) can be released quickly, and this high-entropy designed energy storage ceramic material shows great potential and advantages in the field of lead-free ceramics.

[0124] The ceramic sample with a component of 0.1 in Example 3 exhibits a higher breakdown electric field and energy density, but the energy conversion efficiency is low under a high breakdown electric field. Different from Example 3, the ceramic sample prepared in Example 5 has a process improvement in that 0.5% mol of MnO2 is added to the pre-sintered powder before the second ball milling, and the first ball milling, drying and sieving process are repeated to obtain a powder with uniform particle distribution.

[0125] The ceramic sample prepared in Example 5, the sintering temperature is reduced to 980 ° C, the tetragonal phase P4mm and pseudo cubic phase Coexistence, no other impurities. The grain distribution is more dense, the average grain size is 0.49μm, and the prepared ceramic sample can release the energy storage density W rec 3.7J / cm 3 , the energy storage efficiency η is 70.5%, the breakdown field strength is 330kV / cm, and the relative dielectric constant ε r is 840.1, dielectric loss tanδ is 0.06, and discharge time is 33ns. In addition, MnO2 can reduce Fe 2+ / Fe 3+ The ion exchange between them helps to reduce the leakage current in the material, thereby reducing the energy loss. This embodiment 5 successfully optimizes the energy storage characteristics of the ceramic sample with a component of 0.1 through process improvement.

[0126] In summary, Example 5 is the best example with comprehensive performance. Under the high entropy strategy, it can be seen that when the NN doping amount is 0.1 and an additional 0.5% mol of MnO2 is added, the relaxation behavior of bismuth ferrite-based ceramics can be improved, the growth of grains can be inhibited, the breakdown field strength can be enhanced, and the residual polarization strength can be reduced, thereby obtaining a higher energy storage density of 3.7 J / cm 3 and fast discharge rate of 33ns.

[0127] The present invention is centered around (0.7-x)Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-xNaNbO3-yMnO2, (where 0≤x≤0.15, y is 0 or 0.005, this new material), elaborates on its preparation method, performance testing and potential applications, and provides a reference for further research and industrialization of high entropy ceramic materials.

[0128] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A high entropy designed bismuth ferrite-based energy storage ceramic, characterized in that: The chemical composition of the bismuth ferrite-based relaxor ferroelectric energy storage ceramic is (0.7-x)Bi 0.9 (Sm 0.5 G 0.5 ) 0.1 FeO3-0.3(Sr 0.5 Ba 0.5 )TiO3-xNaNbO3-yMnO2, where 0≤x≤0.15, 0≤y≤0.

005.

2. A high entropy designed bismuth ferrite-based energy storage ceramic according to claim 1, characterized in that: The x is 0, 0.05, 0.10 or 0.15, and the y is 0 or 0.

005.

3. A method for preparing the high entropy designed bismuth ferrite-based energy storage ceramic according to claim 2, characterized in that: The following steps are involved: S1, drying Bi2O3, Sm2O3, Gd2O3, SrCO3, BaCO3, TiO2, Na2CO3, Nb2O5, and Fe2O3, and mixing them according to the proportion to obtain a mixture A; S2, the mixture A obtained in step S1 is subjected to a first ball milling with deionized water and zirconium oxide balls, and then dried after ball milling, and after being completely dried, is passed through a 120-mesh sieve to obtain a mixture B; S3, pre-calcining the mixture B obtained in step S2 at 880°C for 3h, cooling it in the furnace after the temperature drops to 300°C, and then ball-milling it for the second time, drying it, and then passing it through a 120-mesh sieve to obtain a high entropy powder; S4, pressing the high entropy powder obtained in step S3 into a cylindrical ceramic body with a diameter of 10 mm, and sintering it in a muffle furnace at 970° C.-990° C. for 3 hours to obtain a high entropy designed bismuth ferrite-based energy storage ceramic.

4. The method for preparing a high entropy designed bismuth ferrite-based energy storage ceramic according to claim 3, characterized in that: In step S2, during the first ball milling, the planetary ball mill was milled clockwise for 12 hours, and after waiting for 0.5 hours, the ball milling was continued counterclockwise for 12 hours at a rotation speed of 200 r / min. After the ball milling, the ball was dried for 48 hours at a drying temperature of 80°C.

5. The method for preparing a high entropy designed bismuth ferrite-based energy storage ceramic according to claim 3, characterized in that: In the step S3, before the second ball milling, 0-0.5 mol% MnO2 is added to the pre-sintered powder to form a mixture.

6. The method for preparing a high entropy designed bismuth ferrite-based energy storage ceramic according to claim 3, characterized in that: In step S3, during the second ball milling, the planetary ball mill mills clockwise for 12 hours, waits for 0.5 hours, and then continues to mill counterclockwise for 12 hours at a rotation speed of 200 r / min. After the ball milling, the ball is dried for 48 hours at a drying temperature of 80°C.

7. The method for preparing a high entropy designed bismuth ferrite-based energy storage ceramic according to claim 3, characterized in that: In the step S4, the sieved high entropy powder is mixed with 7 wt% of PVA binder to form granules, and then sieved through a 120-mesh sieve again to obtain a ceramic body under a pressure of 158 MPa, with a holding time of 2 minutes.

8. The method for preparing a high entropy designed bismuth ferrite-based energy storage ceramic according to claim 3, characterized in that: In step S4, the specific sintering process is as follows: bury the ceramic body in the same calcined powder, heat the temperature to 970-990°C at a heating rate of 4-6°C / min, sinter for 2-3h, cool the temperature to 300°C, and obtain a high-entropy designed bismuth ferrite-based energy storage ceramic.

9. Application of the high entropy designed bismuth ferrite-based energy storage ceramic as claimed in claim 1 or 2 in high-power dielectric energy storage devices.

Citation Information

Patent Citations

  • Bismuth ferrite-based lead-free high-entropy energy storage ceramic material and preparation method thereof

    CN117594353A

  • A-site co-doped alkaline earth metal and lanthanide perovskite oxygen electrode material and preparation method thereof

    CN118782810A

  • Ferroelectric material and piezoelectric body

    JP2009231482A

  • Capacitative element, integrated circuit and electronic device

    US20070045595A1

  • Lead-free piezoceramic materials

    US8179025B1

Cited By

  • High-entropy rare earth ferrite ceramic material and preparation method thereof

    CN121895029A